Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I don't know how to evaluate it. I know there is one method using the gamma function. BUT I want to know the solution using a calculus method like polar coordinates.

$$\int_{-\infty}^\infty x^2 e^{-x^2}\mathrm dx$$

I will wait for a solution. Thank you.

share|cite|improve this question
Every day I see someone here asking how to "solve" an integral. One does not "solve" integrals. One solves equations; one solves problems. One evaluates integrals. – Michael Hardy Sep 20 '11 at 16:56
I would say calculate or evaluated -- a problem is (if we are lucky) solved, an expression might sometimes be calculated. – AD. Sep 20 '11 at 18:56
Here is a more general question. – J. M. Sep 22 '11 at 12:11
Yes, you don't solve definite_ integrals, you evaluate them. – Stefan Smith Oct 18 '13 at 22:53
The question "How do I find $\int_{-\infty}^\infty e^{-x^2}\,dx$" has been asked and answered on this forum many times. I'm surprised so many people bothered to take the time to type a solution as part of the answer to your question when it has been done before. You can convert your integral to that one using integration by parts, with $dv = xe^{-x^2}dx$ and $u = x$. Also, J.M.'s link answers your question. – Stefan Smith Oct 18 '13 at 22:56

In order to solve the integral by polar coordinates first consider $I_s = \int_{-\infty}^\infty \mathrm{e}^{-s x^2} \mathrm{d} x$. The integral you seek will be obtained by differentiation as $-\left. \frac{\mathrm{d}}{\mathrm{d} s} I_s \right|_{s=1}$.

Now, to evaluate $I_s$:

$$ I_s^2 = \int_{-\infty}^\infty \mathrm{e}^{-s x^2} \mathrm{d} x \cdot \int_{-\infty}^\infty \mathrm{e}^{-s y^2} \mathrm{d} y = \int_{-\infty}^\infty \int_{-\infty}^\infty \mathrm{e}^{-s (x^2 + y^2)} \, \mathrm{d} x \mathrm{d} y $$ Now change variables into polar coordinates $x = r \sin \theta$ and $y = r \cos \theta$. $$ I_s^2 = \int_{0}^{2 \pi} \mathrm{d} \theta \int_0^\infty \mathrm{e}^{-s r^2} \cdot r \, \mathrm{d} r = \pi \int_0^\infty \mathrm{e}^{-s t} \mathrm{d} t = \frac{\pi}{s} $$ where $t = r^2$ change of variable has been made.

Now, since $I_s > 0$ for $s >0$, we obtain $I_s = \sqrt{\frac{\pi}{s}}$.

The integral in question now follows: $$ \int_{-\infty}^\infty x^2 \mathrm{e}^{-x^2} \mathrm{d} x = \left. -\frac{\mathrm{d}}{\mathrm{d} s} \sqrt{\frac{\pi}{s}} \right|_{s=1} = \left. \frac{\sqrt{\pi}}{2} s^{-\frac{3}{2}} \right|_{s=1} = \frac{\sqrt{\pi}}{2} $$

share|cite|improve this answer
Very nice indeed! A solution that yields the value of $\int_{-\infty}^{\infty} x^{2n} e^{-x^2} \mathrm dx$ upon differentiating $n$ times with respect to $s$ and setting $s = 1$... – Dilip Sarwate Sep 20 '11 at 15:21

(As the OP wants a solution without using the gamma function.) Following Davide's suggestion, we write: $$ \int_{-\infty}^{\infty} x^2 e^{-x^2} dx = -\frac{1}{2}\int_{-\infty}^{\infty} x \cdot (-2x e^{-x^2}) dx. $$ Let $u = x$ and $v = e^{-x^2}$. We have $\frac{dv}{dx} = -2xe^{-x^2}$. Integrating by parts: $$ -\frac{1}{2}\int_{-\infty}^{\infty} u \frac{dv}{dx} dx = -\frac{1}{2} \left. uv \right|_{-\infty}^{\infty} + \frac{1}{2} \int_{-\infty}^{\infty} v \frac{du}{dx} dx. $$ I will leave it as an exercise to compute the first term. (Hint: it should come out to $0$. :)) The integral appearing in the second term (ignoring the factor of $\frac{1}{2}$ in the front) simplifies to: $$ \int_{-\infty}^{\infty} v \frac{du}{dx} dx = \int_{-\infty}^{\infty} e^{-x^2} dx. $$ This is the famous Gaussian integral, whose value is $\sqrt{\pi}$. You should now be able to evaluate integral easily.

share|cite|improve this answer

First, since the integrand is symmetric around $0$, we can write it as twice the integral from $0$ to $\infty$. Now, change variables by letting $u=x^2$ so that $du=2xdx$. Then our integral becomes $$\int_{-\infty}^\infty x^2e^{-x^2} dx=\int_{0}^\infty xe^{-x^2} 2xdx=\int_{0}^\infty u^{\frac{1}{2}} e^{-u}du=\Gamma\left(\frac{3}{2}\right) =\frac{\sqrt{\pi}}{2}$$ by the definition of the Gamma function along with the fact that $\Gamma(1/2)=\sqrt{\pi}$. (7 proofs of this last identity, or equivalently the identity $\int_{-\infty}^\infty e^{-x^2}dx =\sqrt{\pi}$ are given on this Math Stack Exchange post.)

share|cite|improve this answer
Thank you. But I want to know solution not using gamma function. – Kim ji hyun Sep 20 '11 at 14:40
@Kim: In any case, you will need to use the fact that $\int_{-\infty}^\infty e^{-x^2}dx =\sqrt{\pi}$. This integral by a change of variables is the same as $\Gamma(1/2)$. Any solution will implicitly be using or proving facts about the Gamma function. – Eric Naslund Sep 20 '11 at 14:42

Detailing Srivatsan Narayanan's solution. It is known that the functional equation of the gamma function may be derived applying the integration by parts technique. Its value at $1/2$ may be evaluated by computing a double integral over the first quadrant in Cartesian and polar coordinates. Let's apply similar ideas in this case. Let $f(x)=x^{2}e^{-x^{2}}$. Since $ f(-x)=f(x)$ the integral $\int_{-\infty }^{\infty }f(x)\mathrm{d}x=2\int_{0}^{\infty }f(x)\mathrm{d}x$. Integrating by parts $$ \int x^{2}e^{-x^{2}}\mathrm{d}x=\int x\cdot xe^{-x^{2}}\mathrm{d}x, $$ since $$ \int xe^{-x^{2}}\mathrm{d}x=-\frac{1}{2}e^{-x^{2}} $$ and $\frac{dx}{dx}=1$, we get $$\begin{eqnarray*} \int x^{2}e^{-x^{2}}\mathrm{d}x &=&x\left( -\frac{1}{2}e^{-x^{2}}\right) -\int -\frac{ 1}{2}e^{-x^{2}}\,\mathrm{d}x \\ &=&-\frac{1}{2}xe^{-x^{2}}+\frac{1}{2}\int e^{-x^{2}}\,\mathrm{d}x.\tag{0} \end{eqnarray*}$$

And so, $$\begin{eqnarray*} \int_{0}^{\infty }x^{2}e^{-x^{2}}dx &=&\left. -\frac{1}{2} xe^{-x^{2}}\right\vert _{0}^{\infty }+\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x \\ &=&\left( \lim_{c\rightarrow \infty }-\frac{1}{2}ce^{-c^{2}}\right) +\frac{1 }{2}0e^{-0^{2}}+\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x \\ &=&0+0+\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x \\ &=&\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x.\tag{1} \end{eqnarray*}$$

Consequently, $$ I:=\int_{-\infty }^{\infty }x^{2}e^{-x^{2}}\mathrm{d}x=2\int_{0}^{\infty }x^{2}e^{-x^{2}}\mathrm{d}x=\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x.\tag{2} $$

To evaluate this last integral we compute the following double integral in Cartesian and polar coordinates ($r^{2}=x^{2}+y^{2}$, $x=r\cos \theta ,y=r\sin \theta $). Since the Jacobian of the transformation $\frac{\partial (x,y)}{\partial (r,\theta )}=r$, we have $$ \int_{x=0}^{\infty }\int_{y=0}^{\infty }e^{-x^{2}-y^{2}}\mathrm{d}x\mathrm{d}y=\int_{\theta =0}^{\pi /2}\int_{r=0}^{\infty }e^{-r^{2}}r\mathrm{d}r\mathrm{d}\theta.\tag{3} $$ Comparing the LHS $$ \int_{x=0}^{\infty }\int_{y=0}^{\infty }e^{-x^{2}-y^{2}}\mathrm{d}x\mathrm{d}y=\left( \int_{0}^{\infty }e^{-x^{2}}\mathrm{d}x\right) \left( \int_{0}^{\infty }e^{-y^{2}}\mathrm{d}y\right) =I^{2}\tag{4} $$ with the RHS $$\begin{eqnarray*} I^2 &=&\int_{\theta =0}^{\pi /2}\int_{r=0}^{\infty }e^{-r^{2}}r\mathrm{d}r\mathrm{d}\theta = \frac{\pi }{2}\int_{0}^{\infty }e^{-r^{2}}r\mathrm{d}r \\ &=&\frac{\pi }{2}\left. \left( -\frac{1}{2}e^{-r^{2}}\right) \right\vert _{0}^{\infty }=\frac{\pi }{2}\left( \lim_{c\rightarrow \infty }-\frac{1}{2} e^{-c^{2}}+\frac{1}{2}e^{-0^{2}}\right) \\ &=&\frac{\pi }{2}\left( 0+\frac{1}{2}\right) =\frac{\pi }{4},\tag{5} \end{eqnarray*}$$ yields $$ I=\frac{\sqrt{\pi }}{2}.\tag{6} $$

share|cite|improve this answer

If you know that $\int_{-\infty}^\infty e^{-x^2}=\sqrt\pi$, then you can use it to easily solve this.

Differentiating $e^{-x^2}$ twice,


Now integral of the left hand side is $0$, as $\int\left(\frac{d^2}{dx^2}e^{-x^2}\right)dx=\frac{d^2}{dx^2}\int e^{-x^2}dx=\frac{d^2}{dx^2}\sqrt\pi=0$.

So integrating, we get

$$\begin{array}{rcl} 0&=&\int -2e^{-x^2}+4x^2e^{-x^2}\,dx\\ &=&-2\sqrt\pi+4\int x^2e^{-x^2}\,dx\\ \implies\int x^2e^{-x^2}\,dx&=&\frac{\sqrt\pi}{2} \end{array} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.